UPAYA PENGELOLA LKP SRIKANDI DALAM MENINGKATKAN KOMPETENSI PROFESIONAL PESERTA TATABUSANA MELALUI PENDEKATAN ANDRAGOGI - Dini Apriani; Ansori Ansori (Comm-Edu (Community Education Journal), 2018)
LKP Srikandi located in Padasuka Cimahi Tengah village, LKP is organizing a superior course program that is the culinary and clothing arrangement. The study aimed to find out whether there is an increase in professional competence of fashion course participants. This research includes qualitative research. The research method used a qualitative method with Andragogy approach. The independent variable is the effort of LKP Srikandi management. While the dependent variable is the improvement of professional competence of course dress participants. The population in the study were all participants of fashion in LKP Srikandi with a sample of 5 dresses course participants. The results of this study (1) show the existence of more pleasing conditions in learning sewing (2) managers are more innovative in providing direction, skills improvement (3) improvement of professional competence of learners in the field of fashion in the form of knowledge progress and understanding of skills gained as well as improvement The three aspects are cognitive, psychomotor and affective.